1996
DOI: 10.1152/jn.1996.76.4.2536
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation by zinc and copper of amino acid receptors from rat olfactory bulb neurons

Abstract: 1. The olfactory bulb contains high concentrations of zinc and copper. Whole cell recording techniques were used to examine the modulatory actions of zinc and copper on N-methyl-D-aspartate (NMDA), gamma-aminobutyric acid (GABA), and glycine receptors on rat olfactory bulb neurons in culture and acutely isolated from adult animals. 2. Zinc and copper were effective antagonists of both NMDA-and GABA-mediated currents. The median inhibiting concentrations (IC50s) for zinc were 19 microM for NMDA receptors and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
88
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 0 publications
14
88
1
Order By: Relevance
“…1) without affecting the distribution or localization of NMDA receptors (data not shown), indicating a direct effect on NMDA receptor function or downstream signaling. Consistent with this, exogenously applied copper can inhibit NMDA receptor-mediated current in hippocampal neurons (24)(25)(26) and can selectively reduce NMDA-mediated potentials and synaptic plasticity in hippocampal slices (27). Importantly, the concentration of copper here shown to protect hippocampal neu- Lysates from injured (L) and uninjured (R) hippocampus of wild-type and Mo br (Ϫ͞Y) littermates were subjected to SDS͞PAGE, transferred to Immobilon P membranes, and stained with primary antibody against spectrin and the caspase 3-dependent p120 cleavage product, as well as the p145 and p150 calpain-dependent cleavage products.…”
Section: Discussionsupporting
confidence: 65%
“…1) without affecting the distribution or localization of NMDA receptors (data not shown), indicating a direct effect on NMDA receptor function or downstream signaling. Consistent with this, exogenously applied copper can inhibit NMDA receptor-mediated current in hippocampal neurons (24)(25)(26) and can selectively reduce NMDA-mediated potentials and synaptic plasticity in hippocampal slices (27). Importantly, the concentration of copper here shown to protect hippocampal neu- Lysates from injured (L) and uninjured (R) hippocampus of wild-type and Mo br (Ϫ͞Y) littermates were subjected to SDS͞PAGE, transferred to Immobilon P membranes, and stained with primary antibody against spectrin and the caspase 3-dependent p120 cleavage product, as well as the p145 and p150 calpain-dependent cleavage products.…”
Section: Discussionsupporting
confidence: 65%
“…Its role in enzyme catalysis and gene expression is well established. More recently it has been demonstrated that copper can regulate brain ligand-gated ion channels (17,18). Here we show that copper is also a potent reversible inhibitor of both water and glycerol transport of the aquaglyceroporin AQP3.…”
Section: Discussionsupporting
confidence: 48%
“…Copper and zinc also modulate other members of the P2X family of receptors, but their effects depend on the receptor subtype. For example, both zinc and copper facilitate the ATP-evoked responses on the P2X 2 receptor (14,15) whereas in the P2X 7 receptor, copper inhibits the ATP-gated currents, whereas zinc is virtually without effect (13). These findings further support the notion that the P2X purinoceptors may have separate metal-binding sites to modulate the channel activity.…”
mentioning
confidence: 52%
“…Zinc is well characterized as a modulator of glutamate neurotransmission, particularly via N-methyl-D-aspartate receptors (1,7). Zinc and copper may also interact with voltage-gated ionic channels and may be important contributors to brain excitability (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation